986-293简便方法

解: 986一297 =986-(300-3) =986-300+3 =686+3 =689

293-(93-29) =(293-93)+29 =200+29 =229 朋友,请【采纳答案】,您的采纳是我答题的动力,谢谢..

812-393-293=800+12-300-93-200-93=(800-300-200)+12-93-93=300+12-100+7-100+7=(300-100-100)+12+7+7=100+26=126

(首项+末项)x项数/2即(984+988)x5/2=5912

430-300+6136 430-300+6=136

429-293=429-300+7=129+7=136

986-175-25=986-(175+25)=986-200=786

98+91+99+84+95+93+97+94+91+96 因84=90-6 =10*90+(8+1+9-6+5+3+7+4+1+6) =900+[8+(1+9)+(5+4+1)+(3+7)] =900+38 =938

原题=986+(2000-1)=986+2000-1=2986-1=2985 或者 原题=(985+1)+1999=985+(1+1999)=985+2000=2985

利用交换律和结合律得,(986+14)(129+171)=700,希望能够对你有帮助.

相关文档

429-293的简便运算
87905-388的简便运算
429-29-i72简便计算
1587-689的简便运算
429-293脱式简便运算
5024-502的简便运算
8904-1297的简便运算
1235 607的简便运算
qyhf.net
5213.net
tongrenche.com
wnlt.net
beabigtree.com
电脑版